"De son sol et de son climat:" National Sport and Landscape in Roland Barthes. Issue 4 (8th August 2021) - Curto, Roxanna
Abstract: This essay considers Barthes' notion of a national sport as an activity that emerges naturally from a country's soil and climate, as explored in his essay from Mythologies, "Le Tour de France comme épopée" (1957) and voiceover narrative to the film, Le Sport et les hommes (1961). In these texts, Barthes explores how certain sports are born from an organic relationship between peoples and landscapes, before becoming codified into a cultural practice through the establishment of rules. He considers the Tour de France (whose playing field is all of France) and hockey in Canada (which developed from the shinny played by children on ponds), to be the two most salient examples of this phenomenon. For Barthes, a national sport is largely an ecological construct, one that reflects the environment of a country and the various ways in which its people inhabit it; national sports are natural sports. In fact, in his analysis of hockey in Canada and the Tour de France, Barthes illustrates how sport can provide a means of imagining an ecological relationship between a people and its environment in which a country's landscape is experienced as a playing field, that is, a space in which nature can be enjoyed and mastered without being destroyed.